Implementation of the principle of sale and purchase transactions through MLM in Brand Branch (BC) PT. Herba Penawar Alwahida Indonesia (HPAI) Tanjungbalai - Asmuni Asmuni; Syahnan Syahnan; Asyura Asyura (Budapest International Research and Critics University, 2020)
Products are